2016
DOI: 10.1002/ldr.2534
|View full text |Cite
|
Sign up to set email alerts
|

Evidence and Causes of Spatiotemporal Changes in Runoff and Sediment Yield on the Chinese Loess Plateau

Abstract: Climate change and human activities are strongly influencing the eco‐hydrological processes of the Chinese Loess Plateau. It is challenging to investigate the spatiotemporal changes of water and sediment yields and identify their potential causes. In this study, we used the annual runoff index (WI) and specific sediment yield (SSY) derived from 58 hydrological stations to quantify the changes and attempted to explain their potential causes. The WI exhibited significant (P < 0.05) decrease ranging from −0.1 to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
49
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 92 publications
(54 citation statements)
references
References 76 publications
(92 reference statements)
4
49
1
Order By: Relevance
“…The historically severe soil erosion in the LP is due to sparse vegetation, intensive rainstorms, erodible loessial soil, steep topography, and a long agricultural history (Rustomji et al, 2008). To control such severe soil erosion, several SWCMs, including terrace and check-dam construction, afforestation and pasture reestablishment, have been implemented since the 1950s (Yao et al, 2011;Zhao et al, 2017). A large ecological restoration campaign, the Grainfor-Green (GFG) project converting farmland on slopes that exceed 25 • to forest and pasture lands, was launched in 1999 (Chen et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The historically severe soil erosion in the LP is due to sparse vegetation, intensive rainstorms, erodible loessial soil, steep topography, and a long agricultural history (Rustomji et al, 2008). To control such severe soil erosion, several SWCMs, including terrace and check-dam construction, afforestation and pasture reestablishment, have been implemented since the 1950s (Yao et al, 2011;Zhao et al, 2017). A large ecological restoration campaign, the Grainfor-Green (GFG) project converting farmland on slopes that exceed 25 • to forest and pasture lands, was launched in 1999 (Chen et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, the sediment yields within the LP have showed a predictable declining trend over the past 60 years (Zhao et al, 2017), resulting in approximately a 90 % decrease in sediment yield in the YR (Miao et al, 2010(Miao et al, , 2011Wang et al, 2016). Many other studies have detected the influences of LUCC and precipitation variability on sediment load changes within the LP.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The construction of check‐dams has progressed rapidly since the 1970s as construction techniques have improved, and the government has implemented numerous projects (Zhao et al, ). Field surveys obtained by the Yellow River Conservancy Committee (YRCC) in 2009 indicated that more than 5,000 large and medium‐sized check‐dams have been constructed in this region, and a large proportion of these check‐dams are sited between Toudaoguai and Longmen stations (see Figure for the locations of these stations).…”
Section: Methods and Datasetsmentioning
confidence: 99%
“…Although the measurement of runoff and sediment using rainfall simulators can be performed in the laboratory (Gholami et al, 2014;Bochet, 2015;Rodrigo Comino et al, 2015b, 2016aSadeghi et al, 2015) and field conditions (Cerdà et al, 2009a;Lieskovský and Kenderessy, 2014;Biswas et al, 2015;Bochet, 2015;Pereira et al, 2015;Ochoa et al, 2016;Rodrigo Comino et al, 2016), field measurements are usually costly and time-consuming work. In addi- tion, different methods of measuring runoff and erosion may lead to non-identical results that are not necessarily related to specific effects on studied variables (Cerdà et al, 2009bSelkimäki et al, 2016;Zhao et al, 2016). Nowadays, the use of rainfall simulators in laboratory and field studies is considered more and more because of their ability to control the intensity and duration of rainfall, which leads to an increase in the accuracy of data (Sadeghi et al, 2015;Davudirad et al, 2016).…”
Section: Introductionmentioning
confidence: 99%